2021
DOI: 10.1111/1750-3841.15774
|View full text |Cite
|
Sign up to set email alerts
|

Properties of transglutaminase‐induced myofibrillar/wheat gluten gels

Abstract: Gelation properties of myofibrillar protein (MP)/wheat gluten (WG) induced by glutamine transaminase (TGase) were studied. Results showed that the inclusion of transglutaminase increased the gel strength, water‐holding capacity (WHC), and nonfreezable water (Wnf) of MP/WG mixture. Circular dichroism (CD) analysis showed that the β‐sheet and random coil content of the MP/WG treated with TGase addition increased by 12.1% and 3.7%, while the α‐helix and β‐turn content decreased by 14.2% and 1.8%. Rheological meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It showed that the addition of CAR can repair the large number of voids in the gel produced by thermal deformation, and therefore, presenting a more regular and orderly gel network structure. However, with the continuous increase of CAR addition (0.5%), the gel network structure inside the gel of minced shrimp gradually changed into a hierarchical network, which may be due to the addition of too high concentration of CAR which changed the surface hydrophobicity of myofibrillar fibrous protein particles and zeta potential and other particles properties ( Ouyang et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…It showed that the addition of CAR can repair the large number of voids in the gel produced by thermal deformation, and therefore, presenting a more regular and orderly gel network structure. However, with the continuous increase of CAR addition (0.5%), the gel network structure inside the gel of minced shrimp gradually changed into a hierarchical network, which may be due to the addition of too high concentration of CAR which changed the surface hydrophobicity of myofibrillar fibrous protein particles and zeta potential and other particles properties ( Ouyang et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The possible reason was that the catalysis of TGase promotes the interaction between myofibrillar protein and non-meat protein Effect, so that the rheological properties of these two non-meat protein composite gels were enhanced. Ouyang, Y [25] proved that Compared with MP/WG system without TGase added, G of the system with TGase added increased more rapidly. This may be due to the formation of stable protein crosslinking structures catalyzed by TGase.…”
Section: Rheological Properties Of Mp Composite Gelling Solutionsmentioning
confidence: 97%
“…Research has shown that non-covalent bonds (hydrogen bonds and hydrophobic interactions) are the most important forces in stabilising animal protein-plant protein complex gels. However, certain studies have also reported that wheat gluten proteins, as plant proteins, do not cross-link with myofibrillar proteins and the interaction between the two proteins must be promoted through TGase to improve their gel properties [52].…”
Section: Protein-protein Interactionmentioning
confidence: 99%